Analisis Kapasitas Saluran Daerah Irigasi Lubuk Buntak Kecamatan Dempo Selatan Kota Pagar Alam - Limbar Alam; Alharia Dinata (JURNAL ILMIAH BERING'S, 2017)
Builders in this irrigation area are a great opportunity to improve the economy of the community Lubuk Buntak. In order to improve and maintain agricultural production of food crops, the Pagar Alam City Government has until now built irrigation facilities and infrastructure both for the construction of new irrigation or rehabilitation in order to support the planned food security program. Irrigation channels located in the Lubuk Buntak irrigation area during the rainy season the water found on the irrigation canal has exceeded the capacity of the irrigation channel so that the irrigation can not work optimally, due to the high rainfall that occurs Thus the irrigation of Lubuk Buntak City Pagaralam irrigation area needs to be analyzed for the rainfall that occurs, in order to determine the ideal irrigation canal design and in accordance with the magnitude of the planned flood discharge, so that the planned irigassi channel works optimally. The purpose of this survey is about Rainfall Analysis, Calculation of planned flood discharge, Irrigation Channel Dimension, in this thesis using five Smirnov-Kolmogorov matching medotas from the calculation of the suitability of the method used is the gumbel method because the maximum difference (Dmax) -4, 70 <from Critical Value 41% (0.41), and analyze flowrate, so that the Irrigation Channel remains optimal for water resources can be utilized according to its designation, based on the parameters obtained. Next, identify the irrigation channel, calculate the intensity of rainfall, determine the flood discharge and the last design the channel dimensions for the area. The research carried out with a land area of ​​50 ha was obtained by the value of the intensity of the 50-year return rainfall of 530.76 m3 / sec, the planned flood return period of 50 years was 1.48 m3 / sec and the design of the channel dimension was (h) = 1, 42 m (B) = 1.40 m, (wf) = 0.29 m, and (TMA) = 1.17m